PENGARUH TEKNIK MEJA BUNDAR TERHADAP HASIL BELAJAR MENULIS TEKS DESKRIPTIF SISWA KELAS VIII MTSN 4 PADANG - Rahma Kurnia Ilahi; Fajrilhuda Yuniko; Fitra Afrida Amna (Universitas Batanghari, 2022)
This study aims to test the effect of the round table technique on students’ achievement in the writing of description texts. The research design of this technique is a quasi-experiment. The experimental group got 80.2, while the control group got 71.08. This study found that students who learned using the Roundtable technique resulted in better descriptive text writing than those who learned using direct instruction techniques. It can be concluded that teaching descriptive text writing using the round table technique gives better results in student writing than direct instruction. The residents are grade II students of MTSN 4 Padang. Two classes were randomly selected as research samples. During treatment, students in the experimental group used the Roundtable technique, while the control group used the direct instruction technique. Analysis of the test results showed that the scores of the experimental group students were higher than those of the control group. In the post-test, the average score of the experimental group got the best results.